Effect of four crop straws on transformation of organic matter during sewage sludge composting - Xiu-lan ZHAO; Bi-qiong LI; Jiu-pai NI; De-ti XIE (Journal of Integrative Agriculture, 2016)
A 45-d laboratory experiment was conducted to compare the effect of four crop straws on the transformations of organic matter (OM) during composting of sewage sludge. The four crop straws included rape straw, wheat straw, maize straw and rice straw. The following parameters such as temperature, OM, humic-like substances (HS), fulvic-like acids (FA) and humic-like acids (HA) were determined. The degradation of OM and the formation of HS and HA could be described well by the first-order kinetic model, while the FA content fluctuated during composting. The maximal degradation rates of OM in the compost piles added with rape straw, wheat straw, maize straw and rice straw were 34.7, 46.9, 54.7 and 52.8%, respectively, and the final contents of HS were 118, 128, 141 and 134 g kg−1, respectively, while the humification indices were higher in the compost piles added with maize straw and wheat straw than in those with rice straw and rape straw. The results indicate that a higher hemicellulose content and a lower C/N ratio in crop straw can result in a higher rate of OM degradation and higher contents of HS, while a higher content of lignin can lead to a higher polymerization degree of humic substances in compost piles. The final compost piles added with maize straw has the highest contents of OM, total nitrogen and humus substance as well as the highest values of polymerization degree, while compost piles with rape straw have the highest potassium content and those with rice straw have the highest pH values.